Exploring Authorship Development Among Mexican EFL Teacher-Researchers (2015)
This article presents a multi-theoretical model to address processes of authorship development in the English as a foreign language teaching profession. Working within a sociocultural perspective of second-language teacher education, the authors examined six experienced nonnative English-speaking teacher-researchers. Perceptions of their key moments in the profession were analyzed using a mixed-method approach that combined document analysis with personal narratives. The findings indicated that both authoring (products and activities in their profession) and self-authorship (transformational processes throughout their careers) contributed to constructing these English as a foreign language professionals as scholars.En este artículo se presenta un modelo multiteórico y multinivel para identificar el proceso en el que los autores se desarrollan en el área de la enseñanza del inglés como lengua extranjera, proceso identificado como desarrollo de la autoría. Este modelo se desarrolló bajo una perspectiva sociocultural de la formación de profesores que presenta una muestra de las percepciones de seis profesores investigadores mexicanos en el área de inglés como lengua extranjera. Se utilizó un método mixto que combinó el análisis de documentos con narrativas personales. Los resultados de esta investigación indicaron la presencia de momentos significativos de su autoría (productos y actividades) y su auto-autoría (procesos de transformación), que contribuyeron a la construcción del desarrollo de la autoría de estos profesores-investigadores.